Acercamiento etnográfico-sociológico a las entrevistas de élite - Venables Brito, Juan Pablo (El Colegio de México, 2024)
This paper presents the experience of gaining access to interviews with individuals from the Chilean political and economic elite for a research study. Within the framework of the work, the importance of scrutinizing elites is justified, followed by an extensive ethnographic account of the events and situations that facilitated the dialogue. Based on this practice and the literature on the subject, the article reflects on the access to this type of interviewees and the aspects that must be considered in the encounter. Furthermore, a different ethical approach is proposed, which may be useful for those who delve into this type of inherently elusive studies.